A study on Enterprise Risk Management (ERM) practices in oil and gas industry / Alia Abdullah Saleh, Al-Hafzan Abdullah Halim and Anas Zafirol Abdullah Halim - Abdullah Saleh, Alia; Abdullah Halim, Al-Hafzan; Abdullah Halim, Anas Zafirol (Research Management Institute (RMI), 2010)
The recent development of oil and gas industry has seen the aggressive and rigorous activities by the organizations directly and indirectly involved in exploration and production of oil and gas. Realizing the importance of risk management of which, once were the secondary activities to the organizations in Malaysia, this dissertation titled "Enterprise Risk Management (ERM) Practices in Oil and Gas Industry" is documented. This first objective of doing this research is to identify the ERM practices in oil and gas industry in particular to PETRONAS Berhad and CNPE Services Sdn Bhd as the case studies. The second objective is to analyze the opinion from personnel on ERM implementation within the oil and gas organization. Analysis for the research comprises of comparative and descriptive approach as well as qualitative analysis which are based on case studies and questionnaire-guided interview. The findings revealed that ERM practices is systematically established, implemented and enforced as part of risk management tool in oil and gas industry in Malaysia. In addition, the opinions gathered from respondents in oil and gas industry shows that ERM practices and implementation are very encouraging. The information is obtained from oil and gas a personnel working in multiple disciplines within the organization comprises of oil and gas operators, consulting companies and service providers, where the results were then thoroughly analyzed. From the observations and findings, the author anticipate that this research would provide better perception to the readers on the scenario of ERM practices within oil and gas industry and the extent of risk management awareness in Malaysia. It is suggested that an in-depth research on the ERM practices are undertaken within the oil and gas industry or related industry to establish the degree of effectiveness and as a benchmark for adoption by the other industries.